Contract law 2.0: 'Smart' contracts as the beginning of the end of classic contract law. Issue 2 (4th May 2017) - Savelyev, Alexander
ABSTRACT: The paper analyzes legal issues associated with the application of existing contract law provisions to so-called Smart contracts, defined in the paper as 'agreements existing in the form of software code implemented on the Blockchain platform, which ensures the autonomy and self-executive nature of Smart contract terms based on a predetermined set of factors'. The paper consists of several sections. In the second section, the paper outlines the peculiarities of Blockchain technology, as currently implemented in Bitcoin cryptocurrency, which forms the core of Smart contracts. In the third section, the main characteristic features of Smart contracts are described. Finally, the paper outlines key tensions between classic contract law and Smart contracts. The concluding section sets the core question for analysis of the perspectives of implementation of this technology by governments: 'How to align the powers of the government with Blockchain if there is no central authority but only distributed technologies'. The author suggests two solutions, neither of which is optimal: (1) providing the state authorities with the status of a Superuser with extra powers; and (2) relying on traditional remedies and enforcement practices, by pursuing specific individuals – parties to a Smart contract – in offline mode.